Insight on Propolis from Mediterranean Countries: Chemical Composition, Biological Activities and Application Fields. Issue 7 (26th June 2019) - El‐Guendouz, Soukaina; Lyoussi, Badiaa; Miguel, Maria G.
Abstract: This review updates the information upon the chemical composition of propolis from all Mediterranean countries as well as their biological properties and applications. The non‐volatile fraction of propolis was characterized by the presence of phenolic acids and their esters and flavonoids. Nevertheless, in some countries, diterpenes were also present: Sicily (Italy), Croatia, Malta, Creta (Greece), Turkey, Cyprus, Egypt, Libya, Algeria and Morocco. The volatile fraction of propolis was characterized by the presence of benzoic acid and its esters, mono‐ and sesquiterpenes, being the oxygenated sesquiterpene β ‐eudesmol characteristic of poplar propolis, whereas the hydrocarbon monoterpene α ‐pinene has been related with the presence of conifers. Regardless the chemical composition, there are common biological properties attributed to propolis. Owing to these attributes, propolis has been target of study for applications in diverse areas, such as food, medicine and livestock. Abstract :